Secoisolariciresinol Diglucoside Regulates Adipose Tissue Metabolic Disorder in Obese Mice Induced by a Western Diet - Shan Dong; Wenliang Bai; Jiaping Chen; Li Zhang; Wanli Sheng; Ronghu Feng (Journal of Food Quality)
Secoisolariciresinol diglucoside (SDG) is the main component of flax lignans. Current studies have reported a positive effect of SDG on obesity and metabolic diseases. SDG has strong blood fat- and blood sugar-lowering, anti-inflammatory, and antioxidant effects and prevents heart disease and other chronic diseases. In this study, we explored the effects of SDG on Western diet-induced obesity and lipid metabolic disorder. Supplementing Western diet-induced obese mice with 40 mg kg1 d1, SDG for 12 weeks significantly reduced body and tissue weights. Increased adiponectin levels and decreased serum leptin and resistin levels were observed in obese mice orally administered SDG. Proliferation of adipose tissue was observed by hematoxylin and eosin staining, and cell size was quantitatively analyzed. As a result, SDG inhibited the proliferation of adipose tissue. In addition, SDG suppressed the mRNA expression of lipid synthetic genes and upregulated the mRNA expression of lipolytic genes. Overall, these results indicate that SDG inhibits obesity induced by a Western diet and regulates adipose tissue metabolic disorder. These results provide a theoretical basis for further study on the regulation of obesity and lipid metabolic disorder caused by SDG.